From fork to fatherhood: Unveiling the link between dietary pattern indices and biochemical parameters of semen - Ali Taheri Madah; Nargesbano Jahangiri; Mahtab Dabagh; Sahar Rostami; Fardin Amidi; Mahshad Khodarahmian; Masoome Jabarpour; Ali Tavoosian; Asma Kheirollahi; Maryam Shabani Nashtaei; Akram Vatannejad (PLoS ONE, 2026)
A cross-sectional design was employed to elucidate the interplay of dietary pattern index scores and seminal and serum biochemical parameters in men presenting to our infertility clinics. Ninety men with idiopathic infertility were enrolled. Semen was collected and evaluated following the World Health Organization (WHO) 2010 guideline for semen analysis (SA). Participants’ dietary habits were evaluated using a 168-item semi-quantitative food frequency questionnaire (FFQ). Independent samples t-tests were performed to compare groups with normal and abnormal semen quality parameters in terms of demographic characteristics, energy intake, and initial semen analysis results. The association between dietary scores—the Alternative Healthy Eating Index (AHEI), the dietary total antioxidant capacity (dTAC), and the dietary inflammatory index (DII)—and semen parameters, specifically total antioxidant capacity (TAC) and tumor necrosis factor-alpha (TNF-α) levels, was investigated using one-way analysis of variance (ANOVA) followed by Tukey’s post hoc tests for multiple comparisons. Higher intake of advanced glycation end products (AGE) was associated with abnormal semen parameters (p = 0.04). No other significant differences in serum/semen biochemistry were detected (all p-values > 0.05). There were no associations between dTAC, AHEI, and DII scores, and TAC or TNF-α (all p-values > 0.05). However, AHEI quartiles showed significant differences in seminal AGE levels (p = 0.002). Semen malondialdehyde (MDA) levels were higher in the abnormal semen group (1.03 ± 0.28 vs. 0.95 ± 0.22; p = 0.09). No associations were observed between dTAC or DII scores and oxidative stress markers (all p-values > 0.05). AHEI quartiles showed a similar pattern in serum MDA and AGE levels. This study adds to the evidence regarding the dietary impact on male fertility.